SAT0193 Macrophages Responding To Mechanical Stress in Scleroderma. (15th July 2016) - Tam, A.; Shiwen, X.; Lopez, H.; Khan, K.; Ahmed-Abdi, B.; Rosario, H.; Arumalla, N.; GIbson, M.; Denton, C.; Abraham, D.; Smith, B.; Stratton, R.
Abstract : Background: Inflammation, vasculopathy and tissue fibrosis are key features of scleroderma (SSc). While healthy forearm skin which has a Young's modulus of 4–12kPa, SSc fibrotic skin measures 50–80kPa with its increased mechanical stiffness 1 . We have shown that mechano-sensing properties of fibroblasts in SSc are mediated by myocardin-related transcription factor A (MRTF-A) 3 . Monocytes/macrophages are likely to be involved in SSc pathogenesis but the effect of mechanical stress on these cells remain to be elucidated 3, 4 . Objectives: To investigate if a mechanically-stressed microenvironment like that in SSc tissue, promotes macrophages towards a pathogenic phenotype, and whether MRTF-A is involved in this process. Methods: Control and scleroderma skin sections were immunostained with anti-CD68 and anti-MRTF-A antibodies (n=3). Human PBMC-derived macrophages were cultured in RPMI/M-CSF on 4kPa and 50kPa collagen-fibronectin-coated plates to mimic "soft"/healthy and "stiff"/fibrotic skin, and activated with LPS (10ng/ml) or IL-10 (10ng/ml) for macrophages designated M(LPS) and M(IL-10) (n=4). MRTF-A expression was assessed by qPCR and conditioned media profiled by Luminex array for inflammatory cytokines. Mouse bone marrow-derived macrophages (BMDMs) of wildtype and MRTF-A-null mice were maintained in RPMI/M-CSF on soft and stiff substrates. The data were analysed by two-way ANOVA and Tukey test (p<0.05, CI 95%). Results: We observed a greater number of CD68 + macrophages in diffuse SSc skin compared to control skin, mainly around perivascular regions. These macrophages also expressed MRTF-A. Human macrophages expressed MRTF-A mRNA and showed differential cytokine expression when cultured on soft and stiff substrates. M(LPS) on soft matrix expressed IFN-γ, which was undetectable with M(LPS) on stiff substrate (mean difference 0.2075±0.1576pg/ml, p<0.01). LPS- and IL-10 activation on soft substrate increased MCP-3 expression compared to controls (mean difference 68.51±49.19pg/ml, p<0.01, 92.88±49.22pg/ml, p<0.0001, respectively). M(LPS) on stiff compared to soft substrate showed lower MCP-3 expression (mean difference 57.01±49.22pg/ml, p<0.05). M(IL-10) on soft substrate showed higher MCP-1 expression compared to controls (mean difference 2448±2232pg/ml, p<0.05). M(IL-10) on stiff substrate decreased expression of MCP-1 (mean difference 2590±2233pg/ml, p<0.05) and increased fractalkine levels compared to soft substrate (mean difference 51.22±36.28pg/ml, p<0.01). Wildtype BMDMs on stiff compared to soft substrate displayed a more elongated morphology. MRTF-A-null BMDMs remained rounded on stiff substrate. Conclusions: MRTF-A is a mechanical stress-responsive factor which co-activates transcription of cytoskeletal and extracellular matrix-modifying genes. MRTF-A may couple mechanical stress to macrophage activation in SSc, where stiff matrix promotes macrophage secretion of cytokines and growth factors that exacerbate fibrosis. References: Sacksen et al., Arthritis Rheum 2013. Shiwen et al., PLoS One 2015. Stifano et al., Curr Rheumatol Rep 2015. Chia et al., Curr Opin Rheumatol 2015. Disclosure of Interest: None declared